The Impact of The Application of The Death Penalty on Reducing Crime Rates: Legal and Criminological Perspectives - Wahyudi, Iwan (Golden Ratio of Data in Summary, 2024)
The application of the death penalty as a punishment for severe crimes has long been a controversial topic in legal and criminological discourse. This article explores the impact of the death penalty's application on reducing crime rates from two main perspectives: law and criminology. This study uses a qualitative approach with in-depth literature analysis of death penalty policies in various countries, as well as empirical data on crime trends before and after the implementation of the death penalty. From a legal perspective, this article examines how the death penalty is justified as the most extreme tool of law enforcement and how it is integrated within the existing legal framework in several jurisdictions. From a criminological point of view, this article examines theories and research that evaluate the effectiveness of the death penalty as a determinant against crime. The analysis includes a study of the psychological effects of the death penalty on potential offenders, as well as a statistical evaluation of the correlation between the death penalty and a decrease in crime rates. The results of the analysis show that although there is some evidence to support the effectiveness of the death penalty as a crime deterrent, this evidence is often inconclusive and influenced by many contextual factors. In addition, we found that the application of the death penalty usually carries significant ethical and social implications, which can limit its effectiveness and acceptance in society. This article concludes with a discussion of the policy implications of these findings. It provides recommendations for law enforcement and policymakers in balancing crime prevention goals with the principles of justice and human rights. We also call for the need for more holistic research to fully understand the impact of the death penalty on crime levels.